(untitled) (Research, Society and Development, 2022)
Despite the importance of the technical responsible (TR) in agro-industries of animal source foods, this function is undervalued, and often can be perceived only as a figurative role, which considerably increases the risk for consumers health who eat products from companies that neglect the role of TR’s. Therefore, the aim of this study was to demonstrate the importance of the TR performance in family agro-industries for the adequacy of these companies to the current legislation. For this purpose, eight family agro-industries located in Rio Grande do Sul with the active role of a technical responsible were analyzed. The analysis of the effect of technicians in responsible for the family agro-industries was carried out in two stages: characterization of family agro-industries through SWOT analysis and analysis of compliance in relation to the Good Manufacturing Practices (GMP), by the checklist of RDC 275/ 2002 applied over eight months of TR attendance. All eight agro-industries showed an increase in the percentage of compliances during the performance of the technician in charge. The overall average increase in compliance was 14.6%. The active monitoring of the TR in agro-industries has directly resulted in an increase in the compliance of the family agro-industries that process products of animal origin, when conducted along with the commitment of the owners and with the support of the local inspection agents.